2019
DOI: 10.1177/0886260519892958
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Romantic Love Myths Questionnaire

Abstract: The purpose of this study was to develop and validate an instrument to measure love myths among Chilean youth. Items created based on review of available literature were refined through experts’ revisions and participant focus groups. The initial questionnaire was applied to 1,538 high school and university students, aged between 14 and 24 years old. Exploratory factor analysis performed with half of the sample led to a 10-item questionnaire, grouped in two factors: idealization and love–abuse. Confirmatory fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
7
0
3
Order By: Relevance
“…These results could be explained by the fact that when one person is in a couple, especially in adolescence, romantic love is idealized and the differences in sexual moral freedoms are intensified according to gender. There are other studies, such as those by Lara et al [ 35 ] and Cava et al [ 36 ], that study romantic love myths and the strength of the couple, or the correlation with dating violence or cyber dating violence, but these were carried out in adolescents with a partner, and the influence of being in or not being in a relationship could not be analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…These results could be explained by the fact that when one person is in a couple, especially in adolescence, romantic love is idealized and the differences in sexual moral freedoms are intensified according to gender. There are other studies, such as those by Lara et al [ 35 ] and Cava et al [ 36 ], that study romantic love myths and the strength of the couple, or the correlation with dating violence or cyber dating violence, but these were carried out in adolescents with a partner, and the influence of being in or not being in a relationship could not be analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Los estudios más recientes realizados con población joven y adolescente de España y Latinoamérica evidencian diferencias estadísticamente significativas entre hombres y mujeres con respecto a la aceptación de los mitos del amor romántico Lara y Gómez-Urrutia, 2019;Nava-Reyes et al, 2018). Los resultados de la presente investigación apuntan en la misma dirección.…”
Section: Discussionunclassified
“…Si bien las investigaciones previas han analizado el ideario del amor romántico en diferentes contextos culturales y geográficos Bosch et al, 2007Bosch et al, , 2013Bosch et al, , 2019Carbonell y Mestre, 2019;Ferrer et al, 2010;Flores, 2019;Lara y Gómez-Urrutia, 2019;Nava-Reyes et al, 2018;Rodríguez-Castro et al, 2013;Singh, 2013), son pocos los estudios que han abordado las creencias sobre el amor en la formación inicial del profesorado (Bonilla-Algovia y Rivas-Rivero, 2018a), a diferencia de lo ocurrido con las creencias sexistas, que han sido mucho más estudiadas en este tipo de muestras (Bonilla-Algovia, 2021;Carretero y Nolasco, 2019;Scandurra et al, 2017). El estudio de Bonilla-Algovia y Rivas-Rivero (2018a), realizado con futuros y futuras docentes de la Comunidad de Madrid, contrastó la vigencia del discurso del amor romántico.…”
Section: Introductionunclassified
“…Although there is a growing body of research on gender representations and their possible links to the acceptance of intimate violence among young people, such as gendered assumptions about sexuality and/or romantic love (OXFAM, 2018; Lara & Gómez-Urrutia, 2019), we found a limited availability of instruments to measure the attitudes behind the acceptance of violence in young people. In their review of several instruments specifically designed to measure attitudes towards dating violence in young people, Exner-Cortens et al (2016) and Jennings et al (2017) showed a relative dispersion in the theoretical constructs behind these instruments, and some issues regarding discriminatory power and reliability on sex-discordant scales and concurrent validity of the set of scales used.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Regarding the trend for psychological aggression toward a romantic partner, it has been explained in terms of it being more subtle and considered by teenagers and young adults as less damaging than its physical or sexual counterparts (Ybarra & Langhinrichsen-Rohling, 2019). In some cases, behaviors such as manipulation, emotional blackmail, or jealousy have been included in the romantic script as a demonstration of romantic interest or even love (Lara & Gómez-Urrutia, 2019; OXFAM, 2018). Experiencing dating violence early in life has important consequences: adolescent victims of dating violence have been reported as more likely to develop mental health issues.…”
Section: Literature Reviewmentioning
confidence: 99%